Retinopathy of Prematurity - Are We Prepared to Face the Third Epidemic? - Akter, Shaheen; Shirin, Mahfuza; Hossain, M Monir (Bangladesh Journal of Child Health, 2010)
DOI: 10.3329/bjch.v30i1.6180 Bangladesh J Child Health 2006; VOL 30 (1/2/3): 25-28